2019
DOI: 10.1016/j.combustflame.2019.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft and MiniCAST soot at the nanoscale

Abstract: Transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), near-edge X-ray absorption fine structure (NEXAFS) and Fouriertransform infrared spectroscopy (FTIR) have been used to compare the nanoscale characteristics of aircraft soot collected at the exhaust of a recent PowerJet SaM146 jet engine, with those of soot generated by a MiniCAST burner. Analyses show that some MiniCAST operating conditions enable generating soot particles of morphology, internal nano-structure and chemical struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 61 publications
3
40
0
Order By: Relevance
“…Marhaba et al. () recently showed that miniCAST soot derived under fuel‐lean conditions, similar to the soot type studied here, constitutes a good analogue to aircraft soot. If real aircraft aggregates behave like the propane flame soot studied here, the enhanced ice nucleation activity of such soot particles resulting from contrail processing could impact subsequent cirrus cloud formation.…”
Section: Atmospheric Implicationssupporting
confidence: 64%
See 1 more Smart Citation
“…Marhaba et al. () recently showed that miniCAST soot derived under fuel‐lean conditions, similar to the soot type studied here, constitutes a good analogue to aircraft soot. If real aircraft aggregates behave like the propane flame soot studied here, the enhanced ice nucleation activity of such soot particles resulting from contrail processing could impact subsequent cirrus cloud formation.…”
Section: Atmospheric Implicationssupporting
confidence: 64%
“…The contribution of cloud-processed soot might be large, given that the fraction of particles emitted by aircrafts undergoing water activation and subsequent freezing is close to unity for visible contrails that form below the threshold temperature where water saturation is reached at upper tropospheric conditions (≤225 K, Kärcher et al, 2015), similar to the scenario studied here. Marhaba et al (2019) recently showed that miniCAST soot derived under fuel-lean conditions, similar to the soot type studied here, constitutes a good analogue to aircraft soot. If real aircraft aggregates behave like the propane flame soot studied here, the enhanced ice nucleation activity of such soot particles resulting from contrail processing could impact subsequent cirrus cloud formation.…”
Section: Contrail Processingmentioning
confidence: 55%
“…However, experiments using particle or droplets sizes that are too large have limited atmospheric relevance. In this paper, we present immersion mode freezing results from experiments with single immersed soot aggregates of atmospherically relevant sizes (<400 nm) of five different BC samples including CAST black and brown carbon which have been used as a proxy for commercial jet engine exhaust emissions (Ess & Vasilatou, 2019; Marhaba et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the SP3 regime has high peak intensities for C 14 H + 10 (m/z 178), C 16 H + 10 (m/z 202), C 18 H + 12 (m/z 228), and C 20 H + 12 (m/z 252), while the relative contributions of heavier PAHs remain comparable. Literature data converge towards the fact that the SP3 set point is distinct from the others in that (i) the organic-to-total carbon ratio is higher (87 % versus ≤ 47 % for the other set points), and (ii) the crystallites of the particles produced in these conditions are significantly smaller and form a distinct disordered arrangement exhibiting many carbon edges (Bescond et al, 2016;Marhaba et al, 2019;Ouf et al, 2016;Yon et al, 2015). Such smaller crystallites suggest that SP3 may undergo nucleation and growth processes different from those of the other set points, subsequently leading to distinct chemical compositions (e.g., different isomeric distributions) of the PM.…”
Section: Multivariate Data Analysis: Principal Component Analysis (Pca)mentioning
confidence: 88%
“…The CAST (Combustion Aerosol Standard) generator is often chosen to produce combustion-generated particles as it is easy to implement for systematic laboratory experiments, with the fuel and oxidation air flows being easily modifiable, enabling the investigation of a variety of chemistries. A miniCAST soot generator operated with different parameters as a source of combustion by-products can mimic some of the physicochemical properties of aircraft emissions, for example (Bescond et al, 2014;Marhaba et al, 2019;Moore et al, 2014). The observations derived from soot produced with this generator hence allows for potential real-world extrapolations, especially for combustion devices not equipped with after-treatment systems.…”
Section: Introductionmentioning
confidence: 99%